Pregled slovenskih virov o plebiscitu 1990 - Osojnik, Janez (Moderna arhivistika, 2023)
The aim of the article is to present the records available for the research of the plebiscite held on December 23, 1990 on the independence of the Republic of Slovenia. We focused on the records held by the Archives of the Republic of Slovenia and those available to researchers in the form of published archival records, diaries and memoirs, and on the internet. The author first briefly outlines the broader context of the developments related to the plebiscite, and then presents archival records relevant to the research on it.
Keywords: 1990; Archives of the Republic of Slovenia, plebiscite, 1990, Republic of Slovenia; Arhiv Republike Slovenije; plebiscit; plebiscite; Republic of Slovenia; Republika Slovenija